Emotions in team contact sports: A systematic review - Campo, M.; Mellalieu, S.; Ferrand, C.; Martinent, G.; Rosnet, E. (The Sport Psychologist, 2012)
This study systematically reviewed the literature on the emotional processes associated with performance in team contact sports. To consider the entire emotional spectrum, Lazarus`s (1999) cognitive motivational relational theory was used as a guiding framework. An electronic search of the literature identified 48 of 5,079 papers as relevant. Anxiety and anger were found to be the most common emotions studied, potentially due to the combative nature of team contact sports. The influence of group processes on emotional experiences was also prominent. The findings highlight the need to increase awareness of the emotional experience in team contact sports and to develop emotion-specific regulation strategies. Recommendations for future research include exploring other emotions that might emerge from situations related to collisions (e.g., fright) and emotions related to relationships with teammates (e.g., guilt and compassion).